2015
DOI: 10.1002/psp4.45
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Development: A Major Piece in the Jigsaw Puzzle of Tumor Size Modeling

Abstract: Mathematical models of tumor size (TS) dynamics and tumor growth inhibition (TGI) need to place more emphasis on resistance development, given its relevant implications for clinical outcomes. A deeper understanding of the underlying processes, and effective data integration at different complexity levels, can foster the incorporation of new mechanistic aspects into modeling approaches, improving anticancer drug effect prediction. As such, we propose a general framework for developing future semi-mechanistic TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Considering the total TS does not allow to capture tumor heterogeneity, then looking for differences across lesions dynamics is a crucial aspect to contemplate when developing new, convincing models of tumor dynamics and, in turn, new treatment paradigms 17. Even though the adoption of more mechanistic models might be discouraged by their complex formulation or limited availability of experimental data, we have shown that the CICIL methodology can be used efficiently to analyze and understand large‐scale datasets prior to modeling, and then guide the modeler in determining the most appropriate approach for a particular case study and for the questions to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the total TS does not allow to capture tumor heterogeneity, then looking for differences across lesions dynamics is a crucial aspect to contemplate when developing new, convincing models of tumor dynamics and, in turn, new treatment paradigms 17. Even though the adoption of more mechanistic models might be discouraged by their complex formulation or limited availability of experimental data, we have shown that the CICIL methodology can be used efficiently to analyze and understand large‐scale datasets prior to modeling, and then guide the modeler in determining the most appropriate approach for a particular case study and for the questions to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This omitted information could be relevant to tumor differentiation or resistance-related mechanisms. 17 In particular, differences among tumor lesions in their response to treatment might provide new quantitative insights on tumor heterogeneity (e.g., genetic/epigenetic alterations, nature of microenvironmental composition, and cell activation states) within a given tissue or among different tissues, 18 and/ or predict differences in disease progression. 19,20 Thus, a tool for comparing lesion dynamics prior to modeling is important to assess whether the total TS can reasonably capture the tumor lesion response.…”
Section: What Is the Current Knowledge On The Topic?mentioning
confidence: 99%
See 1 more Smart Citation
“…Terranova et al. proposed an ODE model incorporating different resistant cell subpopulations allowing the description of both primary and acquired resistance. Here again, the model was not calibrated using real data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MRI, PET, CT, and other imaging systems for cancer diagnosis are ineffective to detect small metastatic tumors because contrast agents used for these diagnostic techniques fail to diffuse into such tumors and stay within them for a sufficient time (59). Fluorescent dyes are also widely used to visualize cancer cells and identify small tumors during intraoperative imaging, but common issues include poor diagnostic properties such as low signal-to-noise ratios and short half-lives in vivo (60).…”
Section: Discussionmentioning
confidence: 99%